2021
DOI: 10.1183/23120541.00267-2021
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound-guided transbronchial biopsy with or without a guide sheath for peripheral pulmonary malignancy

Abstract: Endobronchial ultrasound (EBUS)-guided transbronchial biopsy (TBB) is a common procedure used to diagnose peripheral pulmonary lesions (PPLs). However, existing literature did not conclusively show a difference in the ability of EBUS-TBB with and without a guide-sheath (GS) to diagnose PPLs. This multicenter cohort study enrolled patients presenting for EBUS-TBB of PPLs that finally proved to be malignant. The diagnostic yield and complication rate were compared between patients undergoing EBUS-TBB with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…(25) Our study con rmed this result, with the nding that there was much less moderate bleeding (grade 2 and above) in the GS group (GS vs. conventional: 9.3% vs. 20.8%, p = 0.049). Procedure time results were inconsistent in different studies, with some suggesting that procedure time was longer in the GS group, (33,34) while others indicated it was shorter than with the conventional procedure. (27) In our study, the procedure time was longer in the GS group (GS vs. conventional: 17.6 ± 4.7 min vs. 15.1 ± 4.5 min, p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…(25) Our study con rmed this result, with the nding that there was much less moderate bleeding (grade 2 and above) in the GS group (GS vs. conventional: 9.3% vs. 20.8%, p = 0.049). Procedure time results were inconsistent in different studies, with some suggesting that procedure time was longer in the GS group, (33,34) while others indicated it was shorter than with the conventional procedure. (27) In our study, the procedure time was longer in the GS group (GS vs. conventional: 17.6 ± 4.7 min vs. 15.1 ± 4.5 min, p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…After locating the lesion, withdraw the probe with GS left in situ to ensure the biopsy from the right position. Nevertheless, Kramer and Annema, 70 Ho et al, 77 and Huang et al, 78 clarified that the diagnostic yield did not have an obvious improvement after the introduction of GS, which may be related to the movement or dislodgement of the sheath caused by stiff biopsy tools. 79 On the contrary, Oki et al 80 conducted a multicenter randomized trial showing that histological specimens had a higher diagnostic yield in the GS group (55.3% vs 46.6%, p = 0.033), and the diagnostic yield of upper lobe lesions could be significantly improved upon using GS (63.1% vs 42.9%, p = 0.003).…”
Section: Radial Probe-endobronchial Ultrasonography (Rp-ebus)mentioning
confidence: 99%
“… 9 , 10 Ali et al reported that the diagnostic yield of peripheral lesions by radial endobronchial ultrasound was 72.3% in their meta‐analysis of 25 prospective studies with 2920 lesions, 11 even though a recent report from Huang et al from Taiwan did not show the superiority of using EBUS with GS compared to EBUS without GS. 12 …”
Section: Introductionmentioning
confidence: 99%
“…A guide sheath has the capacity to fix the appropriate bronchus with reduced bleeding as a complication, and radial ultrasonography can detect surrounding tumor directly 7,8 which contributes to an increased diagnosis rate of lung cancer 9,10 . Ali et al reported that the diagnostic yield of peripheral lesions by radial endobronchial ultrasound was 72.3% in their meta‐analysis of 25 prospective studies with 2920 lesions, 11 even though a recent report from Huang et al from Taiwan did not show the superiority of using EBUS with GS compared to EBUS without GS 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation